Human papillomavirus genotypes and factors associated with major cervical smear abnormalities in a sickle cell endemic area of Kisangani, Democratic Republic of the Congo - Yvette Neema Ufoy Mungu; Joëlle Desreux; Elettra Bianchi; Burubu Lisi-Ankiene Junior; Roland Marini Djang’eing’a; Durkin Keith; Artesi Maria; Katenga Bosunga; Vincent Bours (PLoS ONE, 2026)
Background Cervical cancer due to high-risk human papillomavirus (HR-HPV) is the leading gynecological cancer in Sub-Saharan Africa and in the Democratic Republic of the Congo (DRC), where approximately one-quarter of people carries the sickle cell allele. This study aims to identify the HR-HPV genotypes and factors associated with major cervical abnormalities among women living in the sickle cell endemic area of Kisangani, DRC. Methods This hospital-based cross-sectional study consisted to a face-to-face and semi-structured questionnaire for collecting data of the socio-demographic, clinical and sexual behaviors characteristics of participants. The sickle cell status was confirmed using liquid chromatography coupled with mass spectrometry. Cervical smears were collected using the ThinPrep ® Pap-test solution (Hologic Inc, Marlborough, USA). The HR-HPV molecular analysis was performed using the Cobas ® 6800 system (Roche Molecular Systems, Somerville, USA) for real time polymerase chain reaction (RT-PCR) and the Oxford Nanopore platform (Oxford Nanopore Technologies, Oxford, England) for the viral genome sequencing. Cytological analyses were performed using the ThinPrep 5000 processor (Hologic), and the results were reported according to the 2014 Bethesda System classification. The logistic regression model was used to estimate the adjusted Odd ratio (aOR) during the risk factor assessments. Results Among 712 women enrolled, the prevalence of HR-HPV was 28.4% (95% CI: 25.1–31.7). HPV35, HPV52 and HPV31 were the most common genotypes; while the sequencing identified two new variants of HPV103 and HPV223. The following factors were associated with HR-HPV infection: (i) age between 25 and 34 years (aOR: 2.10, 95% CI:1.22–3.69); (ii) being unmarried (aOR: 1.54, 95% CI: 1.05–2.27) and (iii) HIV-positive status (aOR: 14.85, 95% CI: 2.36–288.25). No correlation was observed between hemoglobin AS (HbAS) status and HR-HPV infection or cytological abnormalities. However, women aged 45–54 years (aOR: 3.8, 95% CI: 1.34–11.65), those using intravaginal herbal (aOR: 3.59, 95% CI: 1.26–11.28) and those infected with HPV33 (aOR: 8.45, 95% CI: 1.68–34.05) were more likely to present major cervical abnormalities in our series. Conclusion Our study shows a high prevalence of cervical HR-HPV infection in Kisangani, DRC. HPV35, HPV52, and HPV31 are the three most common genotypes, while novel variants of HPV types 103 and 223 were identified. Our findings also highlight that advanced age, HPV33 infection and intravaginal herbal use are the main factors associated with major cervical abnormalities. Although HbAS has not been associated with HR-HPV infection or cervical lesions, further studies are needed to determine this association in women with sickle cell disease (HbSS).